Pendampingan Petani Jagung Pemula Dalam Penggunaan Pupuk Organik Eco Farming di Desa Tanak Awu Lombok Tengah - Sanapiah Sanapiah; Ade Kurniawan; Yuntawati Yuntawati; Eliska Juliangkary (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
The Patuh Angen Tampok Farmer Group is a farmer group in Tanak Awu Village, Pujut District, Central Lombok Regency, West Nusa Tenggara. This farmer group is known as a pioneering farmer group who harvests watermelons every two years after the rice harvest.However, in its development, watermelon farmers in Tanak Awu Village have experienced losses from year to year. Selling the crops cannot cover the costs incurred by farmers while the watermelons are stored. This is caused by several factors, including (1)the increasing number of farmers growing watermelons outside Tanak Awu Village, and (2) the monopoly of local contractors or buyers which prohibits buyers outside the area from having direct transactions with buyers. farmer. Caused by trade problems in the fields forcing farmers to move their crops outside the area to find buyers. Ofcourse,this adds to the costs that must be borne by farmers. (3) Prices offered by contractors or local buyers are very low. For this reason, five years ago, the Patu Angen Tampok Farmers Group planned to switch to planting corn, because they thought that corn was easier to plant and care for and more profitable. However, this farmer group did not understand the process of planting and caring for and fertilizing, so they did not have the courage to plant corn. What's more, the members of this farmer group are still beginners and don't know where to sell their crops, so they are afraid that no one will buy their crops. The solutions provided to overcome the problems faced by the Patuh Angen Tampok Farmer Group using the Focus Group Discussion (FGD) method are 1) Providing counseling to farmer group participants through Collaboration Partners from corn seed companies to offer expertise regarding the potential advantages of R7 hybrid corn compared to other types of corn, 2) provide counseling to farmer group participants to start switching to natural Eco Farming fertilizers that have been tested the best and the prices are also cheap as an effort to open the horizons of farmers who always rely on chemical fertilizers, and 3) offer assistance to participants of the Patuh Angen farmer organization Tampok Tanak Awu Village in the procedure for planting and caring for corn, and the best environmentally friendly natural agricultural fertilizers. The outcomes that have been produced from this community service activity include: 1) increased expertise of the Patuh Angen Tampok Farmer Group in Tanak Awu Village in the procedure for planting and caring for R7 Hybrid Corn, 2) increasing the ability of the Patuh Angen Tampok Farmer Group participants in making starter and application of Eco Farming Organic Fertilizers, 3) increasing farmers' understanding of the benefits of using organic fertilizers for flora and the survival of microorganisms, 4) Formation of pilot farmer organizations that are starting to realize the advantages ofnatural fertilizers, especially Eco Farming natural fertilizers and may have the capacity to build a marketing network